A sincronia gesto-vocal no funcionamento de linguagem entre mãe e filho de 3 a 26 meses: comparação entre o desenvolvimento de bebês com e sem transtorno do espectro do autismo - Fernández, Gabriela Luisa Gantier (2023)
This longitudinal qualitative research develops the analysis of gesture-vocal synchrony in language functioning between mothers and babies followed from 3 to 26 months of age, one of them with austim spectrum disorder (case R) and the other without ASD (case B) and the other, through filming of six age groups. Moments in which there was greater mother-infant interaction were selected and these excerpts were analyzed using the Eudico Linguistic Annotator software (ELAN), considering multimodal categories of the mothers' and babies' as gestures and speech. The results showed differences in the frequencies and types of gestures between the babies and also in the synchrony between them and their mothers. In case B. there was a gestural and vocal variety of the baby inserted in conjunction relationships between mother and baby in the first year of life, which led to a synchronic production between gesture and speech of the baby in the second year of life, favoring the emergence of the second enunciative mechanism in B. In a different way, in case R, the conjunction relations are not established because the difficulties of the mother in reading discomfort and annoyance gestures that are very present in the baby since its first months of life, hindered the engagement and shared attention of the mother and her baby, disfavoring the inscription of the gesture as language, since the body-language articulation was hindered. As a result, there was a delay in the language acquisition of R. Although the gestural typology of B. and R. are similar, the frequencies, the quality and, above all, the gesture-speech synchrony, differ in the dyads.